International Aspects of Reference and Information Services, 1st edition - Katz, Bill (Routledge, 2020)
This book, first published in 1987, is a stimulating and informative appraisal of the international librarianship scene and the reference service function. Experts discuss how international reference services can be improved to facilitate true exchange of information around the world. They look squarely at problems and provide answers to a host of pertinent questions, such as information counselling and policies, reference services and global awareness, integrating a central reference international studies program, and more.